MiR‐145 regulates myofibroblast differentiation and lung fibrosis. Issue 6 (1st March 2013) - Yang, Shanzhong; Cui, Huachun; Xie, Na; Icyuz, Mert; Banerjee, Sami; Antony, Veena B.; Abraham, Edward; Thannickal, Victor J.; Liu, Gang
Abstract : The expression of smooth muscle actin‐α (SMA‐α) by fibroblasts defines phenotypic transition to myofibroblasts and is a primary contributor to contractile force generation by these differentiated cells. Although the regulation of SMA‐α expression has been the focus of many studies, there is presently only limited information concerning miRNA regulation of lung myofibroblast differentiation and the involvement of these miRNAs in pulmonary fibrosis. To determine the role of miR‐145 in regulating lung myofibroblast differentiation and pulmonary fibrosis. Wild‐type and miR‐145 –/– mice were studied. Lung fibrosis models and cell culture systems were employed. miR‐145 mimics or inhibitors were transfected into pulmonary fibroblasts. Fibrogenic and contractile activities of lung fibroblasts were determined. We found that miR‐145 expression is upregulated in TGF‐β1‐reated lung fibroblasts. miR‐145 expression is also increased in the lungs of patients with idiopathic pulmonary fibrosis as compared to in normal human lungs. Overexpression of miR‐145 in lung fibroblasts increased SMA‐α expression, enhanced contractility, and promoted formation of focal and fibrillar adhesions. In contrast, miR‐145 deficiency diminished TGF‐β1 induced SMA‐α expression. miR‐145 did not affect the activity of TGF‐β1, but promoted the activation of latent TGF‐β1. miR‐145 targets KLF4, a known negative regulator of SMA‐α expression. Finally, we found that miR‐145 –/– mice are protected from bleomycin‐induced pulmonary fibrosis. miR‐145 plays an important role in the differentiation of lung myofibroblasts. miR‐145 deficiency is protective against bleomycin‐induced lung fibrosis, suggesting that miR‐145 may be a potential target in the development of novel therapies to treat pathological fibrotic disorders.—Yang, S., Cui, H., Xie, N., Icyuz, M., Banerjee, S., Antony, V. B., Abraham, E., Thannickal, V. J., Liu, G. miR‐145 regulates myofibroblast differentiation and lung fibrosis. FASEB J. 27, 2382–2391 (2013). www.fasebj.org